Utilization of The Dewantara Kirti Griya Museum as a Learning Resource for Civic Education to Cultivate Creative Thinking Skills - Ambar Sari; Marzuki Marzuki (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to reveal, first, the use of Dewantara Kirti Griya Museum as a learning resource for Civic Education to encourage creative thinking; second, the obstacles encountered in using it as a learning resource for Civic Education to encourage creative thinking; and the third, efforts made to overcome these obstacles. In this study using a qualitative approach with a descriptive type. Determination of research subjects using a purposive technique, for collection data is done by observation, interview and documentation. Data analysis was carried out by interactive analysis, namely data collection, data reduction, data display and conclusion. The results show that, first, Dewantara Kirti Griya Museum can be used as a learning resource for Civic Education through collections, buildings and activities held at the Dewantara Kirti Griya Museum. Second, the obstacles encountered are the lack of museum educators and the insufficient area of the museum building for a large number of visitors. Third, efforts to overcome these obstacles are by utilizing technology, namely providing barcodes in museum collections and using the Grand Hall for activities that invite many participants.